(untitled) (UNED Research Journal, 2013)
Smoking is one of the leading worldwide causes of cardiovascular disease and cancer development, and it not only affects the consumer but also those who are exposed to secondhand smoke. The economic cost of caring for the sick affects resources needed for education and prevention of addiction to cigarettes. This topic has been extensively studied in industrialized countries, but the information from Latin America is less available and seldom is based on inferential statistics applied to clear hypotheses, both central aspects in this article. To test several hypotheses on consumption and characteristics of patients we did an email survey to the entire staff of a state university in Costa Rica (N=2 850) in 2012. A 20% responded in a period of ten weeks and we applied a multiple regression to their answers. The results are statistically consistent with the hypothesis that being single, occupying high job positions and being male lead to increased consumption of tobacco and to an earlier start. To our knowledge, this is the first study using this methodology for the staff of any university in Central America. KEY WORDS Factors associated with smoking, Latin culture and smoking, use of tobacco by university staff, legal drugs, addiction.